Respuesta :

Answer:

m = 3.53972077085

Step-by-step explanation:

-3 × [tex]e^{2m - 5}[/tex] - 3 = -27

Subtracting -3 from both sides of the equation gives;

-3 × [tex]e^{2m - 5}[/tex]  = -24

Dividing by -3 on both sides of the equation gives;

[tex]e^{2m - 5}[/tex] = 8

Let 2m - 5 = x

xloge = 3log2

x = [tex]\frac{3log2}{loge}[/tex] = 2.0794415417

So,

2m - 5 = 2.0794415417

2m = 2.0794415417  + 5

2m = 7.0794415417

Dividing by 2 on both sides of the equation gives:

m = 3.53972077085

ACCESS MORE